Radio-frequency connectors. R.F. coaxial connectors with inner diameter of output conductor 9, 5 mm (0, 374 in) with bayonet lock. Characteristic impedance 50 ohms (Type C) Part 7, (15th December 1996) - British Standards Institution,
No abstract available